Legal Risks in Future Housing Purchase and Sale Contracts: A Case Research in Vietnam - Le Thi, Thao; Le Minh , Thanh (Fakultas Hukum Universitas Lampung, 2024)
A future housing purchase contract stipulates a predetermined sale price between a home buyer and seller, with the transaction set for a future date. This type of contract offers sellers the advantage of price security and continued property use until the sale, mitigating risks associated with market fluctuations and buyer scarcity. Nevertheless, these contracts also present several challenges, particularly the need for clear, transparent terms and careful legal risk management to safeguard the interests of all parties involved. This article uses the method pf analyzing the written law, the method of analyzing the situation trough the researching on secondary sources to analyze anticipated legal challenges in future housing purchase contracts and reviews relevant Vietnamese legal frameworks. It proposes essential contract terms and preventive measures aimed at minimizing risks and protecting the rights of the parties, focusing particularly on the buyer. These insights are intended to guide stakeholders in crafting more secure and equitable future housing purchase agreements.